X‐ray pulsar navigation using multiple detectors based on a new observation strategy. Issue 4 (22nd February 2018) - Guo, Pengbin; Sun, Jian; Xue, Ju
Abstract : Pulsar navigation has gradually attracted increased attention because of its unique advantages in the study of high‐attitude missions and deep space exploration. Low navigation accuracy, due to the long integration period, is one of the main problems with X‐ray pulsar navigation. In this study, a new observation strategy for pulsar navigation that could greatly increase observations compared with the traditional synchronous observation model has been proposed. Due to the uncertainty of the measured angles of the pulsar navigation model, a robust Kalman filter was designed based on the new observation model, and mathematical simulation results showed that the proposed method had improved navigation accuracy.